The Analysis of Productivity Using The American Productivity Center (APC) and Root Cause Analysis (RCA) Method (Case Study: Shodiq Samarinda Tempe Factory) - Sariyani, Dwi Tika; Utomo, Dutho Suh; Sukmono, Yudi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Productivity is one of the components that must be owned by a company to achieve its goals. This study was conducted at Shodiq Tempe Factory which has constraints in maximizing input to achieve optimal output. The purpose of this study was to analyze the level of factory productivity using the American Productivity Center (APC) method. The results of the lowest productivity index calculation were in period 4, which was -1.737%. Then some input productivity that decreased were labor input in period 2 (-23.062%), material input in period 4 (0.623%), and energy input in period 4 (-12.367%). Based on the analysis of the productivity calculation, improvements were made to the decline in productivity using the Root Cause Analysis (RCA) method. From the RCA analysis, several causes were obtained, namely lack of worker discipline, weak supervision, work fatigue, the addition of unnecessary workers, rising soybean prices, poor quality raw materials, contamination of raw materials, energy waste due to the use of electrical equipment and machines that were not properly controlled.